Vagrant virtual development environment cookbook : over 35 hands-on recipes to help you master Vagrant, and create and manage virtual computational environments - Thompson, Chad (Quick answers to common problems., 2015)
If you are a software developer or administrator who wishes to create simple, reusable environments using Vagrant, this book is the perfect choice for you. Whether you are a system administrator with extensive experience in virtualization or a developer wishing to create development scripts for cloud deployment, you will find easy-to-follow recipes and techniques in this book that will allow you to create robust and reproducible virtual environments.